Multivariate analyses of indigenous bread wheat (Triticum aestivum L.) landraces of Oman - Al Lawati, Ali Hussain; Nadaf, Saleem Kaseemsaheb; Saady, Nadiya Abubakar Al; Al Hinai, Saleh Ali; Almamari, Almandhar; Al Maawali, Abdulaziz; Al Maawali, Abdulaziz (Emirates Journal of Food and Agriculture, 2021)
Oman is endowed with enormous diversity of important food crops that have global significance for food security and has ancient history of cultivation of bread wheat (Triticum aestivum L.) with its divergent landraces, which are useful in crop improvement. 55 indigenous Omani accessions conserved at the USDA were evaluated in the winter season (November to April) of the years 2017-2018 and 2018-2019 on loamy soil under sprinklers in augmented design with 5 check varieties in 5 replications following crop husbandry practices as per national recommendations using 9 quantitative (descriptors) and 6 qualitative traits (anthocyanin pigmentation on plant parts). The data on traits were subjected not only for PC values and D values after varimax rotation through Kaiser normalization in Principal Component Analysis (PCA) but also for Agglomerative Hierarchical Clustering (AHC). The results indicated that indigenous bread wheat accessions were significantly different (p>0.05) for all the quantitative traits except number of tillers. The multivariate analyses led to formation of four diverse clusters from PCA analyses corresponding to four quadrants of bi-plot graphs and three clusters from AHC analysis corresponding to main clades of dendrogram. The parents were selected from common accessions of distinct clusters in all the multivariate analyses for hybridization for improving characters of growth for higher yield or productivity with pigmentation on one or two plant parts useful for DUS test of varieties. The indigenous bread wheat landraces / accessions were genetically diverse and have potential for use in national crop improvement programs for earliness and higher grain productivity with distinct identification markers.